Applying the WHO Strategic Approach to Strengthening First and Second Trimester Abortion Services in Mongolia - Tsogt, B.; Seded, K.; Johnson, B. R.; Strategic Assessment Team (2012)
Abortion was made legal on request in Mongolia in 1989, following the collapse of the socialist regime, and later bound by a range of regulations. Concerned about the high number of abortions and inadequate quality of care in abortion services, the Ministry of Health applied the World Health Organization's Strategic Approach to issues related to abortion and contraception in 2003. The aim was to develop policies and programmes to reduce unintended pregnancies, mitigate complications from unsafe abortion, and improve the quality of abortion and contraception services for all socio-economic groups, including adolescents. This paper describes the changes that arose from a strategic assessment, highlighting the introduction of mifepristone-misoprostol for second trimester abortion. The aim was to replace mini-caesarean section and intra-uterine injection of Rivanol (ethacridine lactate), so that second trimester abortions could take place earlier than at 20 weeks gestation. Notional standards and guidelines for comprehensive abortion core were developed, the national pre-service training curriculum was harmonised with the new guidelines, at least one-third of the country's obstetrician-gynaecologists were trained in manual vacuum aspiration and medical abortion, and three model comprehensive abortion care units were established to provide high quality services to women, high quality training for providers and serve as nodes for further scaling up. (c) 2008 Reproductive Health Matters. All rights reserved.